Examining the Role of Eye Movements During Conversational Listening in Noise - Šabić, Edin; Henning, Daniel; Myüz, Hunter; Morrow, Audrey; Hout, Michael C.; MacDonald, Justin A. (Frontiers in Psychology, 2020)
Speech comprehension is often thought of as an entirely auditory process, but both normal hearing and hearing-impaired individuals sometimes use visual attention to disambiguate speech, particularly when it is difficult to hear. Many studies have investigated how visual attention (or the lack thereof) impacts the perception of simple speech sounds such as isolated consonants, but there is a gap in the literature concerning visual attention during natural speech comprehension. This issue needs to be addressed, as individuals process sounds and words in everyday speech differently than when they are separated into individual elements with no competing sound sources or noise. Moreover, further research is needed to explore patterns of eye movements during speech comprehension – especially in the presence of noise – as such an investigation would allow us to better understand how people strategically use visual information while processing speech. To this end, we conducted an experiment to track eye-gaze behavior during a series of listening tasks as a function of the number of speakers, background noise intensity, and the presence or absence of simulated hearing impairment. Our specific aims were to discover how individuals might adapt their oculomotor behavior to compensate for the difficulty of the listening scenario, such as when listening in noisy environments or experiencing simulated hearing loss. Speech comprehension difficulty was manipulated by simulating hearing loss and varying background noise intensity. Results showed that eye movements were affected by the number of speakers, simulated hearing impairment, and the presence of noise. Further, findings showed that differing levels of signal-to-noise ratio (SNR) led to changes in eye-gaze behavior. Most notably, we found that the addition of visual information (i.e. videos vs. auditory information only) led to enhanced speech comprehension – highlighting the strategic usage of visual information during this process.